2005
DOI: 10.1097/01.mib.0000164192.71381.5c
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Facilitates the Repair of Large Colonic Ulcers in 2,4,6-Trinitrobenzene Sulfonic Acid-Induced Colitis in Rats

Abstract: These results indicate that intravenous injection of HGF accelerates colonic mucosal repair and reduces infiltration of inflammatory cells in rats with TNBS-induced colitis and suggest that HGF has the potential to be a new therapeutic modality to promote intestinal mucosal repair in patients with inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Daily subcutaneous injection of Teduglutide, an analogue of GLP-2, has been tried in moderate-to-severe CD patients, which showed potential effect upon mucosal healing [115]. Also, recombinant HGF has been shown to facilitate mucosal repair in a rat colitis model [116]. Human recombinant R-Spondin-1 is another candidate that has been proven to promote proliferation of crypt cells [117].…”
Section: Iecs As Target Cells For the Treatment Of Ibdmentioning
confidence: 99%
“…Daily subcutaneous injection of Teduglutide, an analogue of GLP-2, has been tried in moderate-to-severe CD patients, which showed potential effect upon mucosal healing [115]. Also, recombinant HGF has been shown to facilitate mucosal repair in a rat colitis model [116]. Human recombinant R-Spondin-1 is another candidate that has been proven to promote proliferation of crypt cells [117].…”
Section: Iecs As Target Cells For the Treatment Of Ibdmentioning
confidence: 99%
“…In recent years, a number of basic and clinical studies have focused on growth factors and their role in IBD with the objective of developing a novel therapy (31,33,34,42).…”
mentioning
confidence: 99%
“…since HGF is a potent mitogen for hepatocytes, we confirmed before initiating a human trial that repeated doses of intravenous HGF did not accelerate the development of hepatocellular carcinoma in rats fed a choline-deficient, L-amino acid-defined diet (28). We recently reported that treatment with recombinant HGF stimulates the repair of injured intestinal mucosa, leading to amelioration of experimental colitis (12,13). However, repeated doses of HGF may exhibit oncogenic potential; therefore the carcinogenic potential of HGF should be evaluated as precisely as possible before clinical applications of this agent.…”
Section: Discussionmentioning
confidence: 99%
“…4), and consequently inhibited the development of colitis-associated colorectal cancer (Table II). Although HGF ameliorates mucosal injury through its mitogenic and anti-apoptotic effects on colonic epithelial cells (12,13,30), improvement of the microenvironment, which means the reduction of chronic epithelial exposure to proinflammatory cytokines, growth factors and reactive oxygen species throughout repeated cycles of mucosal injury and repair, is considered to be a primary contributor to the prevention of colitis-associated colorectal cancer.…”
Section: Nο Of Tumors ----------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation